Uma análise dos rendimentos do trabalho entre indivíduos com ensino superior no Brasil - Maurício Cortez Reis; Danielle Carusi Machado (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper provides an analysis of the labor market for individuals with tertiary education in Brazil using data from the 2010 Census. Labor earnings inequality is remarkable among Brazilian workers with a bachelor's degree. Evidence indicates that heterogeneous returns across fields of study and mismatches between the individuals' occupations and their fields of study help to explain part of the labor earnings disparities among workers with tertiary education in Brazil. Also according to the results, the estimated effects associated with these elements seem to be quite different across the labor earnings distribution.
Keywords: I21; J24; J31; 330; tertiary education; fields of study; labor earnings; occupation